Physiological Influence of Stalk Rot on Maize Lodging after Physiological Maturity - Jun Xue; Shang Gao; Liangyu Hou; Lulu Li; Bo Ming; Ruizhi Xie; Keru Wang; Peng Hou; Shaokun Li (Agronomy, 2021)
The stalk lodging caused by stalk rot after physiological maturity (PM) is a major factor restricting further development of mechanical grain harvesting in China. The physiological mechanism of stalk rot on maize stalk lodging after PM is not clear. This study, based on investigating stalk rot under natural field conditions, demonstrated the relation between stalk rot caused by Fusarium spp. and lodging of 35 maize cultivars after PM. In addition, three widely-planted maize cultivars were inoculated with Fusarium spp. at PM to analyze the pathogen of stalk rot causing lodging, by measuring the infection process, carbohydrate contents, and mechanical strength of stalks. Stalk lodging increased by 0.11–0.32% for each 1% incidence of stalk rot. The stalk rot pathogen infected stalks from the pith to the rind. At the level of longitudinal section, the stalk rot pathogen spread from the inoculation internode upwardly and downwardly. These infections gradually increased with the days after PM. Inoculated plants had decreased soluble sugar content; however, cellulose and lignin contained in the inoculated plants were both higher than that in the non-inoculated treatment. Crushing strength was significantly and positively correlated with percentage of soluble sugar. This indicated that the reduction of soluble sugar content during the natural senescence of maize stalk after PM was an important factor for the decrease of stalk strength and the increase of stalk lodging. The occurrence of stalk rot accelerated the decomposition of soluble sugar, which accelerated the decrease of stalk strength and greatly increased risk of stalk lodging.